Analisis Kerugian Out Service High Pressure Heater No.7 Pada PLTU Paiton Unit 2 - Harun Al Rosyid; Wahyu Alghifar Pusipto (JURNAL POWERPLANT, 2014)
Operation of Steam Power (power plant) is highly dependent on the thermal efficiency as a reliability parameter unit. PJB is required to operate and maintain the power plants with world-class quality standards, and is able to maintain the efficiency of the work unit to keep it in optimum condition. In this study used a method in which the actions of this method has the objective to develop the skills, checking, analysis and influence the fuel consumption of the primary to the efficiency of Paiton # 2 due to the application of the inspection work at high pressure heater is no.7.The goal of operate back HPH 7 performance optimal, and calculate the rate of heat transfer coefficient on the concession system.